The Research University in Today's Society - Chan, Gerald (UCL Press, 2017)
In this topical lecture, investor and philanthropist Gerald Chan examines the role of philanthropy in the rapidly changing higher education environment. He proposes that society will be short-changed if the purpose of universities is seen as human resource rather than humanity. Dr Chan argues that the independence of universities is crucial for maintaining the balance between their dual role as engines of the economy and places of curiosity-driven research, and that a philanthropic public private partnership is vital to that. 'Higher education is not cheap; but what is more expensive to society are the consequences of not supporting its universities... In a democratic society, governments come and go, and government funding priorities come and go, but a properly managed endowment endures.' Dr Chan's thought-provoking lecture ranges from pre-Enlightenment beliefs to the invention by Steve Jobs of the first Apple Macs, to demonstrate the vital role of universities to humanity.